Komunikasi Pemasaran Terpadu Dalam Pengembangan Pariwisata Ende Studi Kasus: Festival Danau Kelimutu - Maria Septian Riasanti Mola; Denik Iswardani Witarti (Communication, 2020)
Festival Danau Kelimutu is held every year by the Ende Regency Tourism Office as one of the annual agendas in the promotion of Ende tourism. But this festival has not been able to attract tourists to visit Ende Regency. This study aims to analyze the Integrated Marketing Communication strategy can be implemented for the development of Ende Regency tourism by utilizing the Festival Danau Kelimutu. This research was conducted in a qualitative descriptive manner using case studies. The theory used is Integrated Marketing Communication Theory from Philip Kotler & Gary Arnstrong. The results showed that several stages in integrated marketing communication had actually been carried out,but were less integrated. The Integrated Marketing Communication of the Festival Danau Kelimutu can be designed by determining the target of foreign tourists. Promotional materials and advertisements are also adjusted for international markets. Government public relations activities in the Ende Regency Tourism Office can establish cooperation with the surrounding district governments so that they are more integrated in developing destinations. The parties involved in personal selling are still lacking, so there is a need to provide guidance to improve product knowledge. Ultimately this will support direct selling. The final conclusion of this study is that the tourism potential in Ende Regency can be developed by optimizing existing Integrated Marketing Communication elements.